2013
DOI: 10.5114/pdia.2013.38355
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of atopic dermatitis in infants during the first six months of life: authors’ observations

Abstract: IntroductionAtopic dermatitis (AD) is a frequent chronic skin disease in infants. It creates great difficulties, both diagnostic and therapeutic.AimTo assess the prevalence of atopic dermatitis in infants during the first 6 months of life.Material and methodsThe analysis comprised 2256 children at the age of not more than 6 months, treated at the 2nd Department of Paediatrics and Allergology of the Polish Mother's Memorial Hospital in Lodz, Poland, during seven years. Out of all the patients, children with cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…There are epidemiological and experimental data to substantiate various hypotheses: original hygiene hypothesis: improved hygiene in early life, reduction of family size and number of siblings [4, 5, 14, 15], extended hygiene hypothesis: replacement of traditional anthroposophic way of living, combining elements of conventional medicine (restrictive use of antibiotics, antipyretics and vaccination) with homeopathy and naturopathy (biodynamic diet) by modern lifestyle and new medical recommendations [6, 13, 16, 17]; reduced early exposure to infectious and microbial agents [9, 1724]; shorter period of breast feeding with unfavourable changes in the gut flora [2, 11, 25, 26], first dietary antioxidant hypothesis: antioxidant-depleted Western diet [1, 3, 11, 2729], second dietary antioxidant hypothesis: increased availability of antioxidant-rich (“healthy’’) foods, especially dietary supplements such as vitamins, food preservatives or colorants and traditional Chinese or Vietnamese herbal medicine extracts [1, 30, 31], dietary lipid hypothesis: decreased consumption of saturated animal fat (butter, lard) and oily fish containing long chain n-3 polyunsaturated fatty acids (PUFA), increased intake of margarine, vegetable oils and fast food meals rich in n-6-PUFAs [1, 11, 27, 32, 33], dietary sodium hypothesis: sodium-rich Western diet [11, 24, 34], vitamin D deficiency hypothesis: decreased vitamin D synthesis in skin due to environmental, behavioural and intrinsic factors, in particular reduced exposure to solar radiation because of urban living, indoor occupation, pollution, skin coverage and excessive use of sunscreen for skin cancer prevention [1, 35, 36], vitamin D supplementation hypothesis: delayed side effect of early rickets prophylaxis with vitamin D supplements or excessive maternal concentration of 25(OH)-vitamin D in pregnancy [1, 37–40], maternal diet hypothesis: low maternal vitamin D, antioxidants and 3-ω-PUFAs intake in pregnancy [1, 3, 11, 25],parental smoking during pregnancy and postnatal exposure to environmental tobacco smoke [2, 5, 29, 41...…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are epidemiological and experimental data to substantiate various hypotheses: original hygiene hypothesis: improved hygiene in early life, reduction of family size and number of siblings [4, 5, 14, 15], extended hygiene hypothesis: replacement of traditional anthroposophic way of living, combining elements of conventional medicine (restrictive use of antibiotics, antipyretics and vaccination) with homeopathy and naturopathy (biodynamic diet) by modern lifestyle and new medical recommendations [6, 13, 16, 17]; reduced early exposure to infectious and microbial agents [9, 1724]; shorter period of breast feeding with unfavourable changes in the gut flora [2, 11, 25, 26], first dietary antioxidant hypothesis: antioxidant-depleted Western diet [1, 3, 11, 2729], second dietary antioxidant hypothesis: increased availability of antioxidant-rich (“healthy’’) foods, especially dietary supplements such as vitamins, food preservatives or colorants and traditional Chinese or Vietnamese herbal medicine extracts [1, 30, 31], dietary lipid hypothesis: decreased consumption of saturated animal fat (butter, lard) and oily fish containing long chain n-3 polyunsaturated fatty acids (PUFA), increased intake of margarine, vegetable oils and fast food meals rich in n-6-PUFAs [1, 11, 27, 32, 33], dietary sodium hypothesis: sodium-rich Western diet [11, 24, 34], vitamin D deficiency hypothesis: decreased vitamin D synthesis in skin due to environmental, behavioural and intrinsic factors, in particular reduced exposure to solar radiation because of urban living, indoor occupation, pollution, skin coverage and excessive use of sunscreen for skin cancer prevention [1, 35, 36], vitamin D supplementation hypothesis: delayed side effect of early rickets prophylaxis with vitamin D supplements or excessive maternal concentration of 25(OH)-vitamin D in pregnancy [1, 37–40], maternal diet hypothesis: low maternal vitamin D, antioxidants and 3-ω-PUFAs intake in pregnancy [1, 3, 11, 25],parental smoking during pregnancy and postnatal exposure to environmental tobacco smoke [2, 5, 29, 41...…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated an increase in the prevalence of asthma, allergic rhinitis (AR) and atopic dermatitis (AD) over the last four decades, particularly in children. This increase has been observed in both industrialized and developing countries [ 1 6 ]. World Health Organization estimates that 400 million people suffer from AR and 300 million from asthma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Other studies have utilised electronic medical records 7,8 seeking a diagnosis by an attending physician, while others relied on parentreported physician diagnosis, where parents were typically asked "Has your child been diagnosed with eczema?". [9][10][11][12] Some studies have employed direct examination of the child by a health care professional, [13][14][15][16] while others have combined more than one of these methods. 13,15 It is unknown if these methods are comparable.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms occur in 45% of patients within the first 6 months of life, and face and neck are involved in more than 90% of them. Another point to note is that 60% of infants and children with this disease recover up to 12 years of age and rarely persist until adulthood 2 , 3 .…”
mentioning
confidence: 99%